Usability and clinical efficacy of diabetes mobile applications for adults with type 2 diabetes: A systematic review. (September 2017) - Fu, Helen; McMahon, Siobhan K.; Gross, Cynthia R.; Adam, Terrence J.; Wyman, Jean F.
Highlights: Diabetes app efficacious. Greater interactivity greater effect. Usability varied. Abstract: Objectives: To assess the usability and clinical effectiveness of diabetes mobile applications (diabetes apps) developed for adults with type 2 diabetes. Method: A systematic review of the usability and effectiveness of diabetes apps was conducted. Searches were performed using MEDLINE, EMBASE, COMPENDEX, and IEEE XPLORE for articles published from January 1, 2011, to January 17, 2017. Search terms included: diabetes, mobile apps, and mobile health (mHealth). Results: The search yielded 723 abstracts of which seven usability studies and ten clinical effectiveness studies met the inclusion criteria from 20 publications. Usability, as measured by satisfaction ratings from experts and patients, ranged from 38% to 80%. Usability problem ratings ranged from moderate to catastrophic. Top usability problems are multi-steps task, limited functionality and interaction, and difficult system navigation. Clinical effectiveness, measured by reductions in HbA1c, ranged from 0.15% to 1.9%. Conclusion: Despite meager satisfaction ratings and major usability problems, there is some limited evidence supporting the effectiveness of diabetes apps to improve glycemic control for adults with type 2 diabetes. Findings strongly suggest that efforts to improve user satisfaction, incorporate established principles of health behavior change, and match apps to user characteristics will increase the therapeutic impact of diabetes apps.